Immunotherapy Targeting Myeloid-Derived Suppressor Cells (MDSCs) in Tumor Microenvironment - Gao, Xidan; Sui, Hongshu; Zhao, Shang; Gao, Xingmei; Su, Yanping; Qu, Peng (Frontiers in Immunology, 2021)
Abstract Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that accumulate in tumor-bearing hosts to reduce T cells activity and promote tumor immune escape in the tumor microenvironment (TME). The immune system in the TME can be stimulated to elicit an anti-tumor immune response through immunotherapy. The main theory of immunotherapy resides on the plasticity of the immune system and its capacity to be re-educated into a potent anti-tumor response. Thus, MDSCs within the TME became one of the major targets to improve the efficacy of tumor immunotherapy, and therapeutic strategies for tumor MDSCs were developed in the last few years. In the article, we analyzed the function of tumor MDSCs and the regulatory mechanisms of agents targeting MDSCs in tumor immunotherapy, and reviewed their therapeutic effects in MDSCs within the TME. Those data focused on discussing how to promote the differentiation and maturation of MDSCs, reduce the accumulation and expansion of MDSCs, and inhibit the function, migration and recruitment of MDSCs, further preventing the growth, invasion and metastasis of tumor. Those investigations may provide new directions for cancer therapy.